IMPROVING LITERACY SKILLS THROUGH STRENGTHENING THE QUALITY OF SCHOOL-BASED EDUCATION - Asykur, Muamar; Mirwan, Mirwan; Halik, Sampara (Nurul Jadid University, 2022)
The problem of literacy is one of the problems that must receive special attention from the people of Indonesia. This is because, in the last few decades, the competitiveness of Indonesian people has tended to be less competitive, one of which is due to the crisis of literacy culture. This literacy culture crisis is often related to quality in an educational institution. Thus, this study aims to understand strategies to improve the literacy skills through strengthening the quality of school-based education. This research uses a qualitative approach with a case study type. The data in the study were obtained through observation, interviews and documentation techniques. The data is then analyzed using the Miles and Huberman data analysis technique which consists of data reduction, data display, and verification. The results of the study show that quality improvement oriented towards achieving literacy skills in students is carried out by; 1) reward and punishment for students, 2) teacher competence development, 3) learning orientation based on learning processes and outcomes, 4) teacher mastery of technological media, and 5) library visits.